Extraction of extracellular polymeric substances (EPS) from indigenous bacteria of rare earth tailings and application to removal of thorium ions (Th4+) - Han, Jianhong; Li, Hongyan; Liu, Yi; Liu, Pai; Song, Yi; Wang, Yuting; Zhang, Lianke; Wang, Weida (Water science and technology, 2023)
Thorium, as an important radioactive element, is widely present in nature, and its accompanying environmental pollution is also serious. Extracellular polymeric substances (EPS) are commonly found on the surface of microbial bodies and have strong adsorption capacity for metal ions. In this study, four methods were used to extract EPS from indigenous bacteria of rare earth tailings and to determine the best extraction method. The extracted EPS was applied to treat Th4+, and the changes in functional groups and composition of EPS were investigated. The results showed that the ultrasonic method was more efficient than other methods. The best removal efficiency was observed at pH 3.5, Th4+ concentration of 20 mg/L, and EPS dosage of 30 mL at 25 °C. After 9 h, the adsorption process reached equilibrium with a maximum removal efficiency of 75.93% and a maximum theoretical adsorption capacity of 25.96 mg/g. The Th4+ removal process was consistent with the Langmuir and Freundlich adsorption isotherms and the kinetic data were consistent with the pseudo-second-order kinetic model, which is mainly based on chemisorption. Amide I and amide II of proteins, C–H from aliphatic, as well as O–H and C = O from carboxylic acid play important roles in the adsorption process.